Cause and management of hamstring injuries in college sprinters - A qualitative approach - Shah, A. J.; Iftakhar, M. T. (Journal of Sports Medicine & Doping Studies, 2017)
Despite to investigate the possible existence hamstring injuries of college sprinters are common and incidence rates have not declined in recent times. Furthermore sprinting is known as fastest activity so hamstring with respect to injury location, tissue and muscle associated with correct diagnosis based with history on time as well adequate knowledge to the athletes are equally essential. Additionally high rate of hamstring tightness and pain was unknown, while increasing pain may lead to accumulated muscle damage.